PSYCHIC ERASURE: PSYCHODYNAMICS AND FEMALE SELF-MAKING IN MEENA KANDASAMY’S WHEN I HIT YOU - Sharma, Himmat; Kashyap, Tanu; Vashisht, Ashu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
In this research paper, the notion of psychic erasure will be analyzed as gendered dynamics of internalized silence and fragmentation in When I Hit You by Meena Kandasamy. Outgrowing the largely socio political interpretations of marital violence, the analysis predicts the psychodynamic aspects of oppression to claim that the institution of patriarchal power is not only executed by means of extrinsic control, but also by the systematic degradation of female subjectivity. Here the psychic erasure is theorized as an inhibition, perversion and re-arrangement of memory, identity, and affect in circumstances of the coercive relationality. The paper is based on a feminist psychodynamic framework, which incorporates the knowledge of psychoanalysis, trauma theory as well as feminist narratology in further analysis of how the novel depicts the fragmented consciousness of the protagonist in terms of narrative discontinuities, repetition and meta fictional self-reflexivity. These formal tactics are viewed to be inscriptions of trauma and not just a stylistic experimentation. Simultaneously, the paper shows the role that writing plays as a counter discursive practice that turns repression into articulation and vulnerability into agency. The analysis will be done in two phases where tracing the processes by which intimate partner violence generates psychic disintegration, internalized subordination and analyzing how narrative self-fashioning generates a process of resistant self-making. By so doing the paper locates autobiographical writing as a psychodynamic act of recreation, a process whereby silenced experiences are both re-signified and re-inserted into the cultural discourse. The study adds to the feminist literary analytical literature by providing a sensitive description of the way interiority is created, broken, and re-created within the patriarchal environment. It suggests that the story of Kandasamy not only reveals the operations of psychic erasure, but applies its reversal, thus reformulating female authorship as a type of epistemic and affective resistance.